Interaction of small molecules with the SARS-CoV-2 main protease in silico and in vitro validation of potential lead compounds using an enzyme-linked immunosorbent assay. (December 2020) - Pitsillou, Eleni; Liang, Julia; Karagiannis, Chris; Ververis, Katherine; Darmawan, Kevion K.; Ng, Ken; Hung, Andrew; Karagiannis, Tom C.
Graphical abstract: Highlights: The SARS-CoV-2 M pro is an important viral target for the ongoing COVID-19 pandemic. Initial screen by docking 300 small molecules to the M pro active site. Preferential binding of 3 leads to the M pro active site revealed by blind docking. Stability of lead compounds with the M pro active site confirmed by MD simulations. Hypericin and cyanidin-3-O-glucoside inhibit M pro in vitro in micromolar range. Abstract: Caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the COVID-19 pandemic is ongoing, with no proven safe and effective vaccine to date. Further, effective therapeutic agents for COVID-19 are limited, and as a result, the identification of potential small molecule antiviral drugs is of particular importance. A critical antiviral target is the SARS-CoV-2 main protease (M pro ), and our aim was to identify lead compounds with potential inhibitory effects. We performed an initial molecular docking screen of 300 small molecules, which included phenolic compounds and fatty acids from our OliveNet™ library (224), and an additional group of curated pharmacological and dietary compounds. The prototypical α-ketoamide 13b inhibitor was used as a control to guide selection of the top 30 compounds with respect to binding affinity to the M pro active site. Further studies and analyses including blind docking were performed to identify hypericin, cyanidin-3-O-glucoside and SRT2104 as potential leads. Molecular dynamics simulations demonstrated that hypericin (ΔG = -18.6 and -19.3 kcal/mol), cyanidin-3-O-glucoside (ΔG = -50.8 and -42.1 kcal/mol), and SRT2104 (ΔG = -8.7 and -20.6 kcal/mol), formed stable interactions with the M pro active site. An enzyme-linked immunosorbent assay indicated that, albeit, not as potent as the covalent positive control (GC376), our leads inhibited the M pro with activity in the micromolar range, and an order of effectiveness of hypericin and cyanidin-3-O-glucoside > SRT2104 > SRT1720. Overall, our findings, and those highlighted by others indicate that hypericin and cyanidin-3-O-glucoside are suitable candidates for progress to in vitro and in vivo antiviral studies.